2011
DOI: 10.1158/0008-5472.can-10-3213
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming Temozolomide Resistance in Glioblastoma via Dual Inhibition of NAD+ Biosynthesis and Base Excision Repair

Abstract: Glioblastoma multiforme (GBM) is a devastating brain tumor with poor prognosis and low median survival time. Standard treatment includes radiation and chemotherapy with the DNA alkylating agent temozolomide (TMZ). However, a large percentage of tumors are resistant to the cytotoxic effects of the TMZ-induced DNA lesion O 6 -methylguanine due to elevated expression of the repair protein O 6 -methylguanine-DNA methyltransferase (MGMT) or a defect in the mismatch repair (MMR) pathway. Although a majority of the T… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
116
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(120 citation statements)
references
References 45 publications
4
116
0
Order By: Relevance
“…In addition to suppressing antitumor immune responses and promoting cell survival and cell motility, trp metabolism may thus also constitute a novel metabolic mechanism to confer resistance of tumor cells to radiochemotherapy. This metabolic pathway may explain why NAD þ -depleting agents, such as FK866, are of limited efficacy in some tumors such as malignant gliomas and neuroblastomas, where quinolinic acid has been shown to be proproliferative (56,57). The resistance mechanism, as suggested by our data, seems to be regulated at the level of QPRT, which is why this enzyme may be a novel therapeutic target in malignant gliomas.…”
Section: Discussionmentioning
confidence: 70%
“…In addition to suppressing antitumor immune responses and promoting cell survival and cell motility, trp metabolism may thus also constitute a novel metabolic mechanism to confer resistance of tumor cells to radiochemotherapy. This metabolic pathway may explain why NAD þ -depleting agents, such as FK866, are of limited efficacy in some tumors such as malignant gliomas and neuroblastomas, where quinolinic acid has been shown to be proproliferative (56,57). The resistance mechanism, as suggested by our data, seems to be regulated at the level of QPRT, which is why this enzyme may be a novel therapeutic target in malignant gliomas.…”
Section: Discussionmentioning
confidence: 70%
“…4C; Yang et al 2007;Pittelli et al 2010). Previous studies have shown that FK-866 can dramatically enhance MMS-induced cell death in numerous mammalian cell types (Yang et al 2007;Goellner et al 2011). We treated control and ALKBH7-depleted cell lines with MMS, followed by the addition of FK-866 at a concentration that does not itself result in cell death within the time span of the experiment.…”
Section: Alkbh7-dependent Necrotic Cell Death Genes and Development 1093mentioning
confidence: 99%
“…DNA damageinduced necrosis is characterized by the hyperactivation of NAD + -dependent poly-ADP-ribose polymerase (PARP), which leads to intracellular NAD + depletion, loss of ATP production, mitochondria depolarization, generation of reactive oxygen species (ROS), and eventual loss of total cellular bioenergetics (Ha and Snyder 1999;Cipriani et al 2005;Alano et al 2010;Tang et al 2010;Goellner et al 2011;Luo and Kraus 2012). In addition to mitochondrial dysfunction, severe DNA damage can induce the translocation of the apoptosis-inducing factor (AIF) from the mitochondria to the nucleus, where AIF forms a DNAdegrading complex with histone H2AX and cyclophilin D (Yu et al 2002;Baritaud et al 2010).…”
mentioning
confidence: 99%
“…GMX1777 is a soluble prodrug of GMX used for in vivo studies (5,6). NAMPT inhibitors, including GMX1778 (GMX) and FK866, have shown preclinical activity alone and in combination with several therapeutic DNA-damaging agents, but the mechanism of synergy has not been clearly elucidated (7)(8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%